Analysis of the Implementation of Website-Based Digital Employee Attendance (HRGAIS) at PT David Roy Indonesia - Muqi Mathil Adllil Melsa; Marsofiyati Marsofiyati; Maulana Amirul Adha (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the implementation of a website-based digital employee attendance system at PT David Roy Indonesia, including the obstacles encountered and efforts made to optimize its application. The study uses a qualitative descriptive method with a case study approach. Data collection techniques included interviews with five informants consisting of operational employees and Human Resources (HR) staff, observation, literature study, and documentation. The results of the study show that the implementation of a website-based digital attendance system at PT David Roy Indonesia has been carried out well and has facilitated employee attendance administration. The procedures for using the system are considered practical and easy to understand. Supporting factors for implementation include ease of access, automatic attendance recording, and support from HR. However, there are still several obstacles, such as technical disruptions at certain times, dependence on internet connection, and the process of employee adjustment to the new system. This study is expected to serve as material for the evaluation and development of digital attendance systems to be more effective and sustainable.